Legal instruments for risk management in agriculture in the new Common Agricultural Policy - Lipińska, Izabela (Przegląd Prawa Rolnego, 2021)
The subject of the article is issues related to risk management in agriculture that may arise in connection with the implementation of the new Common Agricultural Policy. The question to answer is whether the regulations proposed at the EU level make the implementation of the necessary legal instruments possible and whether these instruments support agricultural producers and contribute to their protection in the aspect of the priorities of the CAP. The findings of the research conducted allow to assess the proposed legal solutions positively. The EU model of CAP implementation, based on the subsidiary principle and result-oriented, may contribute to a wider application of particular legal instruments of risk management. The legal solutions proposed in Poland correspond to the assumptions of the CAP. However, it seems that insurance as a basic management instrument will continue to be used insufficiently. The lack of legal regulations concerning the creation of mutual funds is still a weakness when it comes to the approach to the Polish model of risk management.